Women’s Principle and the Issue of Universal Guilt in the Novel Petruša and Miluša by Petar Sarić - Jeftimijević Mihajlović, Marija (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The main characteristic of the novel Petruša i Miluša by Petar Sarić is an elaborate narrative scheme in the form of two voices, mother’s and daughter’s, two stories that flow and intertwine, and build a third—a story about a story. With this novel and its specific structure, Sarić, on one hand, continued the formal refinement that begun in his previous novels. On the other hand—on the issue of basic poetic-philosophical assumption connected to the question of personal and general (metaphysical) human guilt—he went further concerning both his creative work and the entire Serbian prose with similar thematic preoccupations. The Dionysian principle is represented by the imperatives of the body, the laws of blood, and Petruša’s instinctive reaction, through her unrestrained nature that, at the same time, strives for self-renewal and self-destruction. It is a form of the female principle—creative and destructive at the same time, dark, chthonic as opposed to Miluša’s Apollonian orientation, worshiping of light, and her mental illumination. Petruša i Miluša is not a model of a family novel (although it can be assumed). Still, in Sarić’s novel, the family is just a focus into which the courses of overall existence converge and in which things are condensed and reflected by their true dimensions. This fact is not at all surprising bearing in mind his previous novels (Sutra stiže Gospodar, and especially Dečak iz Lastve), Sarić has already proved himself as a writer who searches for the deepest secrets of human nature, introducing a reader to the dark realm of the human soul, which is shaped according to his artistic creation and creative intuition.